Transition anionic complex in trihexyl(tetradecyl)phosphonium-bis(oxalato)borate ionic liquid – revisited. Issue 10 (9th March 2021) - Shimpi, Manishkumar R.; Rohlmann, Patrick; Shah, Faiz Ullah; Glavatskih, Sergei; Antzutkin, Oleg N.
Abstract : A Transition Anionic Complex (TAC) was formed and passed into [P6, 6, 6, 14 ][BOB] when Li[BOB] (but not Na[BOB]) was used in the synthesis, significantly altering ILs' properties. The TAC transformed into [BOB] − in the IL upon heating at 413 K for 1 h. Abstract : It was found that Li[BOB]· n H2 O salts were not readily suitable for the synthesis of high-purity orthoborate-based tetraalkylphosphonium ionic liquids, as exemplified here for trihexyl(tetradecyl)phosphonium bis(oxalato)borate, [P6, 6, 6, 14 ][BOB]; along with [BOB] −, a metastable transition anioni c complex (TAC) of dihydroxy(oxalato)borate with oxalic acid, [B(C2 O4 )(OH)2 ·(HOOC–COOH)] −, was also formed and passed into the ionic liquid in the course of the metathesis reaction with trihexyl(tetradecyl)phosphonium chloride. On the contrary, Na[BOB] was found to be a more suitable reagent for the synthesis of this IL, because [BOB] − anions safely passed into the final IL without hydrolysis, when metathesis reactions were performed using aqueous-free media. Since ultra-pure Na[BOB] is not commercially available, in this work, a preparation protocol for ultra-pure (>99%) Na[BOB] was developed: (i) molar ratios of boric and oxalic acids were optimised to minimise boron-containing impurities, (ii) the Na[BOB] product was thoroughly purified by sequential washing of a fine powder product in hot acetonitrile and ethanol and (iii) characterised using powder X-ray diffraction and solid-state 11 B MAS NMR spectroscopy. The physico-chemical properties of the prepared boron-impurity-free IL, i.e., its density, viscosity, electric conductivity, glass-transition temperature and thermal stability, were found to be significantly different from those of the previously reported [P6, 6, 6, 14 ][BOB], containing ca. 45 mol% of TAC, [B(C2 O4 )(OH)2 ·(HOOC–COOH)] − . It was found that a high-purity [P6, 6, 6, 14 ][BOB] prepared in this work has a considerably lower viscosity, a higher viscosity index and a wider electro-chemical window (ECW) compared to those of the sample of [P6, 6, 6, 14 ][BOB] with ca. 45 mol% of TAC. Interestingly, [B(C2 O4 )(OH)2 ·(HOOC–COOH)] − in the latter sample almost completely transformed into [BOB] − anions upon heating of the IL sample at 413 K for 1 hour, as confirmed using both 11 B and 13 C NMR. Therefore, in this work, apart from a well-optimised synthetic protocol for boron-impurity-free [P6, 6, 6, 14 ][BOB], implications of boron-containing transition anionic complexes in tetraalkylphosphonium-orthoborate ILs used in different applications were highlighted.